The effects of tropical cyclones on characteristics of barrier layer thickness - Zhang, Zheliang; Ma, Zhanhong; Fei, Jianfang; Zheng, Yunxia; Huang, Jiancheng (Frontiers in Earth Science, 2022)
The impact of tropical cyclones on the characteristics of barrier layer (BL) thickness is investigated in this study in combination with observations and numerical simulations. Statistical results based on Simple Ocean Data Assimilation reanalysis (SODA) data and Argo float measurements reveal a significant effect of TCs on the BL characteristics. The BL thickness increases remarkably with the TC approaching, reaches its maximum 1-5 days after the TC passage, and recovers to its pre-storm state within 30 days on average. The peak increase in BL thickness is slightly rightward biased relative to the TC track, reaching 1.31 m (26.93%) relative to the pre-storm state as revealed by SODA data. The changes in BL thickness show a strong correlation with TC characteristics in terms of intensity and translation speed, tending to be more significant with more intense or slower-moving TCs. The thickening of isothermal layer on the right of TC tracks and shallowing of mixed layer act together to determine the BL development. The three-dimensional Price– Weller–Pinkel (3DPWP) ocean model is applied to explore the influence of precipitation on BL thickness. The results show that the precipitation tends to decrease the mixed layer depth while the vertical mixing of TCs deepens the isothermal layer depth, both of which act together to increase the BL thickness.